Risk Measure and Premium Distribution on Catastrophe Reinsurance (Communications in Mathematical Research, 2021)
In this paper, we propose a new risk measure which is based on the Orlicz premium principle to characterize catastrophe risk premium. The intention is todevelop a formulation strategy for Catastrophe Fund. The logarithm equivalent formof reinsurance premium is regarded as the retention of reinsurer, and the differentialearnings between the reinsurance premium and the reinsurer's retention is accumulated as a part of Catastrophe Fund. We demonstrate that the aforementioned riskmeasure has some good properties, which are further confirmed by numerical simulations in R environment.